Identification of PVTGS (Particularly Vulnerable Tribal Groups) Habitat at Kawardha District in Chhattisgarh State - Dixena, Durgesh; Kumar, Dilip; Singh, P R; Patel, DK (International Journal of Computer Sciences and Engineering, 2025)
The present study was conducted in the Kawardha district of Chhattisgarh state, because in this district Baiga population is highest as compare to other district of state. For primary data collected the researcher surveyed three gram Panchayat namely, Bairak, Dholbazza and Borakhakar of Kawardha district. On the basis of discussion with Baigas, it may be said that Baigas living on higher hill, have retained more of their traditional features then the ones in lower areas who have mostly migrated from the top in search of cultivable land, when Bewar practice was forcibly stopped by the government. The 1912 Mandla Gazeteer noted that the ‘principal habitat’ of Baiga lie in the ‘recesses of the Maikal range’, which stretches from Kawardha district of Chhattisgarh to some part of Madhya Pradesh